2021
DOI: 10.1101/2021.04.12.21255313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strategies and action points to ensure equitable uptake of COVID-19 vaccinations: A national qualitative interview study to explore the views of undocumented migrants, asylum seekers, and refugees

Abstract: Introduction Early evidence confirms lower COVID-19 vaccine uptake in established ethnic minority populations, yet there has been little focus on understanding vaccine hesitancy and barriers to vaccination in migrants. Growing populations of precarious migrants (including undocumented migrants, asylum seekers and refugees) in the UK and Europe are considered to be under-immunised groups and may be excluded from health systems, yet little is known about their views on COVID-19 vaccines specifically, which are e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 25 publications
(23 reference statements)
2
54
0
Order By: Relevance
“…For some migrants and ethnic minority groups, consistent use of social media platforms for sharing and receiving COVID-19-related health information was reported in several included studies 29 34-36 40-42 44 43 . Social media was reported to be the preferred source of information about COVID-19 for international migrants in China (WeChat was used by 94.5% of respondents for COVID-19 information).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…For some migrants and ethnic minority groups, consistent use of social media platforms for sharing and receiving COVID-19-related health information was reported in several included studies 29 34-36 40-42 44 43 . Social media was reported to be the preferred source of information about COVID-19 for international migrants in China (WeChat was used by 94.5% of respondents for COVID-19 information).…”
Section: Resultsmentioning
confidence: 83%
“…An additional eight studies were conducted in the US, 32-39 and one each in China, 40 Jordan, 41 Qatar, 42 and Turkey. 43 Eight studies reported on migrants, 27 29 32 40-44 including migrants in the host countries of China 40 , Jordan 41 , Quatar, 42 Turkey 43 , and the US 32 and UK 27 29 , and one study involved predominantly migrants from Venezuela residing in other countries. 44 Nine studies reported about a specific ethnic minority or group (Latino individuals, 32 34 36 37 Black American citizens, 35 39 , Jain community members 28 and Syrian migrants 41 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[32] Easy access will be important to facilitate vaccination uptake for those with risk due to occupation or comorbidity[24]. Our study and others certainly indicated that many would prefer a local, low risk community healthcare setting with convenience of booking appointments[29, 41, 42]. However, a key difference to note is that at the time of data collection, access to vaccines was not a tangible issue as they had not yet been approved.…”
Section: Discussionmentioning
confidence: 95%